Implementasi Sistem Informasi Bongkar Muat KIP INNI Pada PT. Gusti Glori Sukses Pangkalpinang - Harrizki Arie Pradana; Melati Suci Mayasari; Yuyi Andrika; Akbar Fitriansyah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
In managing the administrative data of loading and unloading production suction vessels at PT. Gusti Glori Sukses still uses manual administrative data management. All recapitulation of company administrative documents is still archived on sheets of paper, document preparation is still manual, which is considered less effective and efficient. Because data collection is still inaccurate, the effect on report presentation and administrative data processing tends to be slow. So that PT. Gusti Glori Sukses wants to have an information system for managing the loading and unloading administrative data of production suction vessels that is accessed internally which makes it easier for the company to run the company's operations smoothly. An information system that is made must be effective and in accordance with needs. The research method used in the development of this information system uses object-oriented design and analysis methods, with the FAST model, and the tools used are the Unified Modeling Language (UML). With the implementation of the information system for loading and unloading production suction vessels at PT. Gusti Glori Sukses based on computerization, all problems faced can be resolved, so that the administration of loading and unloading production suction boats can run optimally so that it becomes more effective and efficient.